Preparation method and application of efficient polydopamine photo-thermal evaporation modified film
By co-depositing dopamine in the nanogel, the problem of poor evaporation performance of existing photothermal evaporation films when using polydopamine is solved, and high-efficiency photothermal conversion and evaporation performance are achieved.
Patent Information
- Application Number
- CN202411620427.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-14
- Publication Date
- 2025-03-07
AI Technical Summary
When using polydopamine (PDA), existing photothermal evaporation films are rarely studied in depth, resulting in limited development in the field of photothermal evaporation and poor evaporation performance.
A highly efficient polydopamine photothermal evaporation modified film preparation method is adopted to increase its load density per unit volume by co-depositing dopamine inside the nanogel. The method includes dissolving polymer A in solvent A, forming a nanoparticle dispersion, and forming a porous nanogel membrane through a suction filtration process, and then co-depositing dopamine on its surface.
The high-efficiency polydopamine photothermal evaporation modified film prepared by this method has a photothermal conversion efficiency of 91.01-114.10% under one solar illumination condition, and the photothermal evaporation amount is 1.34-1.68kg·m-2·h-1, which significantly improves the photothermal evaporation performance.
Smart Images

Figure CN119570106A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of water treatment product preparation, and in particular to a method for preparing a high-efficiency polydopamine photothermal evaporation modified membrane and its application. Background Art
[0002] Efficient access to freshwater resources is a critical requirement for sustainable water resource utilization. Desalination is an effective means of addressing water shortages. Commonly used desalination technologies, such as reverse osmosis, electrodialysis, multi-effect flash evaporation, and vapor compression, consume significant amounts of fossil fuels and increase greenhouse gas emissions. Solar thermal evaporation, a novel technology for collecting water vapor for desalination, uses solar energy to generate heat and vaporize water. It holds great potential for application in this area.
[0003] With the development of technology, polydopamine has received more and more attention as a photothermal conversion material. The reasons are mainly divided into three aspects: First, polydopamine (PDA) has similar physical and chemical properties to natural melanin and has certain photothermal conversion performance. There are 5,6-indolequinone (DHI) and 5,6-dihydroxyindole (IQ) conjugated light-absorbing structures inside polydopamine. The chemical interaction between DHI and IQ forms an electron donor-acceptor pair, which reduces the energy band gap of PDA and makes it have photothermal conversion performance; second, dopamine (DA) and polydopamine are ideal materials for molecular assembly and chemical modification. DA molecules have PDA polymers have amino, phenolic hydroxyl, benzene ring, and catechol structures in addition to the above structures. A variety of modifiable functional groups in molecules and polymers can react with almost all types of materials through hydrogen bonds, π-π, metal coordination interactions, Michael addition and Schiff base reactions, including low surface energy materials that are difficult to modify, such as polytetrafluoroethylene; thirdly, the preparation process of polydopamine is simple and mild. Dopamine monomers can be successfully prepared by dissolving in a weak alkaline aqueous solution at room temperature for a certain period of time, and are easy to mass produce; therefore, using polydopamine as a photothermal conversion material for photothermal steam conversion research has considerable prospects.
[0004] However, unlike biomacromolecules such as proteins and nucleic acids, which often rely on sequence-controlled, step-by-step synthetic reactions, the dopamine polymerization process involves a series of random polymerization reactions of intermediate molecules and their supramolecular stacking. This complex reaction mechanism results in an excessively low content of molecules with light-absorbing structures within PDA, ultimately resulting in PDA's photothermal conversion performance far inferior to that of carbon materials or polypyrrole. Furthermore, the complexity of the dopamine polymerization reaction mechanism makes it extremely difficult to regulate PDA's photothermal conversion performance.
[0005] In summary, most existing photothermal evaporation films use PDA as an additive to bond high-absorbency polymers or inorganic materials, and there is little in-depth research on its photothermal evaporation performance, which limits the development of PDA in the field of photothermal evaporation and results in poor evaporation performance of existing photothermal evaporation films. Summary of the Invention
[0006] The purpose of the present invention is to provide a method for preparing and applying an efficient polydopamine photothermal evaporation modified film, aiming to solve the technical problem that most photothermal evaporation films in the prior art use PDA as an additive to bond high-absorbency polymers or inorganic materials, and rarely conduct in-depth research on its photothermal evaporation performance, which limits the development of PDA in the field of photothermal evaporation and leads to poor evaporation performance of existing photothermal evaporation films.
[0007] To achieve the above object, the present invention adopts a method for preparing a high-efficiency polydopamine photothermal evaporation modified film, comprising the following steps:
[0008] Step 1: dissolving polymer A in solvent A to obtain solution A, and adding solution A dropwise into solvent B with stirring to obtain a dispersion of polymer A nanoparticles;
[0009] Step 2: assemble a commercial microfiltration membrane in a filtration cup and pour the polymer A nanoparticle dispersion into it, completely filter the polymer A nanoparticle dispersion to obtain polymer A nanoparticle aggregates on the surface of the commercial microfiltration membrane;
[0010] Step 3: Pour solvent A into a filtration cup containing a commercial microfiltration membrane and polymer A nanoparticle aggregates and completely filter out solvent A to obtain a swollen polymer A on the surface of the commercial microfiltration membrane; Pour solvent B into a filtration cup containing a commercial microfiltration membrane and a swollen polymer A and completely filter out solvent B to obtain a polymer A nanogel porous membrane on the surface of the commercial microfiltration membrane;
[0011] Step 4: dissolving dopamine hydrochloride in solvent B to obtain solution B; dissolving silane coupling agent A and anhydrous ferric chloride in solvent C to obtain solution C;
[0012] Step 5: Mix solution B and solution C and disperse them evenly to obtain solution D;
[0013] Step 6: Immerse the polymer A nanogel porous membrane with a commercial microfiltration membrane substrate in solution D and react with constant temperature and oscillation. After the reaction is completed, wash it to obtain a high-efficiency polydopamine photothermal evaporation modified membrane on the surface of the commercial microfiltration membrane.
[0014] Step 7: Immerse the high-efficiency polydopamine photothermal evaporation modified membrane with a commercial microfiltration membrane substrate into solvent D, completely dissolve the commercial microfiltration membrane with solvent D, and finally obtain a self-supporting high-efficiency polydopamine photothermal evaporation modified membrane, which is then preserved.
[0015] Wherein, the polymer A is at least one of polyvinylidene fluoride, polyethersulfone, polypropylene and polyamide, and has a molecular weight of 0.40Mda;
[0016] The solvent B is at least one of water, ethanol and acetone;
[0017] The solvent A is one or more of N,N-dimethylformamide, N-methylpyrrolidone, dimethylacetamide, and dimethyl sulfoxide;
[0018] The solvent C is at least one of water, ethanol and acetone, with a mass fraction of at least one of 75%, 90% and 98%, and the amount is 5 to 15 mL;
[0019] The solvent D is at least one of formic acid, N-methylpyrrolidone and dimethylacetamide, with a mass fraction of 88%.
[0020] Among them, in step 1:
[0021] The amount of solvent A is as follows: polymer A: solvent A = 0.1-1.5g: 50-200mL;
[0022] The amount of solvent B used is based on the amount taken from solution A: solvent B = 1-10 mL: 200 mL;
[0023] In step 3: the amount of solvent A is 5 to 20 mL;
[0024] In step 3: the amount of solvent B is 100-300 mL;
[0025] In step 4, the amount of solvent B used is: dopamine: solvent B = 0.1-0.5 g: 50-200 mL.
[0026] Among them, in step 4:
[0027] The dosage of anhydrous ferric chloride is as follows: anhydrous ferric chloride: solvent B = 0.05-0.5g: 50-200m;
[0028] The silane coupling agent A is at least one of KH-550, KH-560, KH-570, and KH-580, and the dosage is silane coupling agent A: solvent C = 0.05-0.20 g: 50-200 mL.
[0029] Among them, in step 1:
[0030] When dissolving polymer A in solvent A, the process is carried out under heating and stirring conditions. Since polymer A is dissolved under heating conditions, the resulting solution A needs to be cooled to room temperature before being added dropwise to solvent B.
[0031] Room temperature is 20-30℃;
[0032] The stirring speed is 50-200 rpm;
[0033] The dropping speed is 4-6 mL / min.
[0034] Wherein, in step 2 and step 3: the filtration vacuum pressure is 0.55-1.00 bar;
[0035] In step 4: the dissolution process is carried out by stirring, and the stirring rate is preferably 150 rpm;
[0036] In step 5: after mixing solution B and solution C, the dispersion method used is ultrasound, and the ultrasound conditions are: ultrasound power 120-180W, ultrasound time 2-5min;
[0037] In step six:
[0038] The constant temperature shaking method is a constant temperature water bath shaking, with a temperature of 40-60°C, a shaking frequency of 90-180 rpm, and a time of 18-24 hours;
[0039] The cleaning method is to rinse repeatedly with deionized water until the eluent shows no color change.
[0040] Among them, in step seven: the microfiltration membrane dissolution method is to immerse the membrane in solvent D for 24 hours, then take it out and replace the solvent, and then immerse the membrane in solvent D again for 24 hours after replacement, and repeat the above operation process 4 times.
[0041] Among them, in step seven: the method for preserving the high-efficiency polydopamine photothermal evaporation modified membrane is to immerse the membrane in deionized water, and replace the deionized water every 48 hours during the preservation process.
[0042] Wherein, the commercial microfiltration membrane is a nylon microfiltration membrane or a polytetrafluoroethylene microfiltration membrane.
[0043] The high-efficiency polydopamine photothermal evaporation modified membrane prepared by the method described above is applied to seawater desalination.
[0044] The present invention provides a method for preparing and applying a high-efficiency polydopamine photothermal evaporation modified membrane. This method proposes, for the first time, a method for co-depositing polydopamine (PDA) photothermal materials within nanogels, significantly increasing the loading density of polydopamine per unit volume, thereby preparing a high-efficiency PDA photothermal evaporation modified membrane. When the high-efficiency polydopamine photothermal evaporation modified membrane prepared by this method is actually used, the polydopamine photothermal evaporation modified membrane is placed at a 45° angle to the horizontal plane. At this time, under an illumination of 1 sun (1kW·m -2) under the conditions of photothermal conversion efficiency of 91.01-114.10%, and photothermal evaporation capacity of 1.34-1.68 kg·m -2 ·h -1 In this way, the technical problem that most of the existing photothermal evaporation films use PDA as an additive to bond high-absorbency polymers or inorganic materials, and there is little in-depth research on its photothermal evaporation performance, which limits the development of PDA in the field of photothermal evaporation and leads to poor evaporation performance of existing PDA photothermal evaporation films is solved. BRIEF DESCRIPTION OF THE DRAWINGS
[0045] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the following briefly introduces the drawings required for use in the embodiments or the description of the prior art. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.
[0046] Figure 1 It is a schematic diagram of the preparation process of the high-efficiency polydopamine photothermal evaporation modified membrane in the present invention.
[0047] Figure 2 Schematic diagram of the morphology of the PVDF nanogel membrane in the present invention under dry and wet conditions.
[0048] Figure 3 This is a diagram showing the test results of the atomic force microscope (AFM) PF-QNM mode of the PVDF nanogel membrane (wet state) of the present invention and the commercial PVDF microfiltration membrane.
[0049] Figure 4 It is a microscopic morphology of the membrane surface of a commercial PVDF microfiltration membrane and related embodiments and comparative examples of the present invention.
[0050] Figure 5 It is the X-ray photoelectron spectroscopy (XPS) broad spectrum of the films obtained in Example 1(a) and Comparative Example 1(b) of the present invention.
[0051] Figure 6 Schematic diagram of the distribution and content of iron (Fe) elements on the membrane surface obtained in the examples and comparative examples of the present invention.
[0052] Figure 7 1 and 2 are digital photos of the films obtained in Example 1 and Comparative Example 1 of the present invention under dry and wet conditions, and a schematic diagram of the light absorption rate of each film.
[0053] Figure 8 It is a schematic diagram of the photothermal performance and separation efficiency of the membranes obtained in the relevant embodiments and comparative examples of the present invention.
[0054] Figure 9It is a cross-sectional microscopic image of the membrane obtained in the relevant embodiments and comparative examples of the present invention. DETAILED DESCRIPTION
[0055] The embodiments of the present invention are described in detail below. Examples of the embodiments are shown in the accompanying drawings. The embodiments described below with reference to the accompanying drawings are exemplary and are intended to be used to explain the present invention, but should not be understood as limiting the present invention.
[0056] See also Figures 1-9 :
[0057] in Figure 1 Schematic diagram of the preparation process of the high-efficiency polydopamine photothermal evaporation modified membrane in the present invention; it can be seen that the present invention first prepares a PVDF nanogel porous membrane, and then co-deposits polydopamine inside the gel in the gel porous membrane to prepare a high-efficiency polydopamine photothermal evaporation modified membrane;
[0058] in Figure 2 Schematic diagram of the morphology of the PVDF nanogel membrane in the present invention under dry and wet conditions; Figure 2 Middle: a is the microscopic morphology of the membrane under wet conditions (scanning electron microscope (SEM) test, model: TESCAN MIRA4; the morphology of the membrane after freeze-drying under wet conditions, the volume and shape of the membrane under freeze-drying conditions remain basically unchanged); b is the microscopic morphology of the membrane under dry conditions (SEM, heating and drying); c is the macroscopic morphology of the membrane under wet and dry conditions (digital photos). As shown in Figure a, the microstructure of the membrane under wet conditions is relatively loose, and a clear pore structure can be seen; as shown in Figure b, the microstructure of the membrane under dry conditions is compact, and no pore structure is found; the digital photo in Figure c shows that the membrane has a large area and is transparent under wet conditions, while the area of the membrane is greatly reduced under dry conditions, and the membrane changes from a transparent state to a white opaque state; the above situation indicates that during the drying process, the volume of the microstructural units (nanogels) in the membrane may have been significantly reduced, or the distance between the microstructural units has been significantly shortened, resulting in the microstructure of the membrane changing from loose to compact;
[0059] in Figure 3 1. It is a graph showing the test results of the atomic force microscope (AFM) PF-QNM mode of the PVDF nanogel membrane (wet state) of the present invention and the commercial PVDF microfiltration membrane; Figure 3In the figure, a is the morphology of PVDF nanogel membrane and the PF-QNM modulus test results; b is the morphology of commercial PVDF microfiltration membrane and the PF-QNM modulus test results; it can be seen from Figure a that the average DMT modulus of the membrane surface under wet conditions is 3.16GPa; it can be seen from Figure b that the average DMT modulus of the commercial PVDF microfiltration membrane surface is 7.45GPa. Therefore, the contact deformation of PVDF nanogel membrane under wet conditions is significantly greater than that of commercial PVDF membrane (DMT modulus describes the elastic behavior of the material under contact deformation conditions), indicating that the membrane material formed in the present invention is obviously "soft", reflecting that the membrane material is a loose polymer cross-linked structure. Since the definition of gel is: polymers are connected to each other under certain conditions to form a spatial network structure, and the structural gaps are filled with liquid as a dispersion medium. Therefore, the membrane material under wet conditions is a nanogel structure, combined with Figure 3 The phenomenon that the macroscopic volume of the membrane is greatly reduced under dry conditions in b can confirm that the PVDF membrane prepared by the present invention is composed of nanogel;
[0060] in Figure 4 It is a microscopic morphology of the membrane surface of commercial PVDF microfiltration membrane and the relevant embodiments and comparative examples of the present invention. Figure 4 In the figure, a is the surface micromorphology of a commercial PVDF microfiltration membrane; b is the surface micromorphology of the membrane of comparative example 1; c is the surface micromorphology of the membrane of example 2; d is the surface micromorphology of the membrane of example 1; e is the surface micromorphology of the membrane of example 3; f is the surface micromorphology of the membrane of example 4; Figures ab reflect that the commercial PVDF microfiltration membrane is porous, and after co-deposition (Figure b), the microstructure of the membrane has not changed significantly. As can be seen from Figure cf, as the volume of PVDF DMF solution added to water gradually increases during the preparation of PVDF nanoparticles (gradually increasing from 1 mL to 8 mL), the micromorphology of the polydopamine modified membrane gradually changes from a loose porous structure to a dense non-porous structure.
[0061] in Figure 5 is the X-ray photoelectron spectroscopy (XPS) broad spectrum of the films obtained in Example 1(a) and Comparative Example 1(b) of the present invention; Figure 5 It can be seen that the content of fluorine (F) in the polydopamine photothermal evaporation modified film obtained by the present invention is significantly lower than that in the conventional co-deposited film. Since both Example 1 and Comparative Example 1 use polydopamine to modify PVDF, and only PVDF contains fluorine among the materials used in the relevant modifications, the fluorine content in the film obtained by the present invention is significantly lower than that in the conventional modified film, proving that the polydopamine content in the film obtained in Example 1 is significantly higher than that in the conventional co-deposited film.
[0062] in Figure 6 Schematic diagram of the distribution and content of iron (Fe) on the membrane surface obtained in the embodiment and comparative example of the present invention. Figure 6 In the figure, a is the distribution and content of Fe elements on the membrane surface obtained in comparative example 1; b is the distribution and content of Fe elements on the membrane surface obtained in example 2; c is the distribution and content of Fe elements on the membrane surface obtained in example 1; d is the distribution and content of Fe elements on the membrane surface obtained in example 3; e is the distribution and content of Fe elements on the membrane surface obtained in example 4; it can be seen that the Fe element content in the modified membrane obtained in comparative example 1 (Figure a) is significantly reduced compared to the Fe element content in the membrane obtained in the present invention (Figure be). Since the co-deposition methods of the embodiment and the comparative example are consistent, both have an Fe element doping step, and the content of Fe elements in the membrane can reflect the amount of polydopamine loaded. Obviously, the polydopamine loading in the membrane obtained by the present invention is significantly higher than that of the traditional co-deposition membrane. In addition, it can be seen from Figure be that as the volume of the DMF solution of PVDF added to water gradually increases during the preparation of PVDF nanoparticles (gradually increasing from 1 mL to 8 mL), the Fe element content in the membrane finally obtained gradually increases. This is because the increase in volume causes the PVDF content to gradually increase in the initial stage of membrane preparation, and the amount of PVDF gel in the final membrane gradually increases, ultimately allowing more polydopamine to co-deposit in the membrane;
[0063] in Figure 7 1 is a digital photograph of the films obtained in Example 1 and Comparative Example 1 of the present invention under dry and wet conditions and a schematic diagram of the light absorptivity of each film; Figure 7 In the figure, a is a digital photograph of the film obtained in Example 1 under dry conditions; b is a digital photograph of the film obtained in Comparative Example 1 under dry conditions; c is a digital photograph of the film obtained in Example 1 under wet conditions with an illumination intensity of 1 sun; d is a digital photograph of the film obtained in Comparative Example 1 under wet conditions with an illumination intensity of 1 sun. It can be seen that the films obtained in the present invention under dry and wet conditions are significantly darker than the conventional co-deposited films (Figures a-d). Testing using an ultraviolet-visible-infrared spectrometer reveals (Figure e) that the films obtained in the present invention under dry and wet conditions have stronger light absorption capabilities than the conventional co-deposited films.
[0064] in Figure 8 Schematic diagram of the photothermal performance and separation efficiency of the membranes obtained in the relevant embodiments and comparative examples of the present invention; Figure 8 Where a is the temperature of pure water and the membranes obtained in the relevant examples and comparative examples under 1 sun illumination (1kW·m -2) (the illumination time is 30 minutes, and the membrane surface temperature is measured after it stabilizes. A solar simulator is used to generate simulated sunlight, and the model of the solar simulator is 7ILX500P; a thermal imager is used to test the membrane surface temperature, model: FlukeTiS65); b is the relationship between the amount of water evaporation of pure water and the membranes obtained in the relevant embodiments and comparative examples under 1 sun illumination and time; c is the water evaporation rate and photothermal conversion efficiency of the membranes obtained in the relevant embodiments and comparative examples under 1 sun illumination; d is the separation efficiency of the membrane obtained in Example 1 for salt ions in simulated seawater; it can be seen from Figure a that the surface temperature of the membrane obtained by the present invention is significantly higher than that of the traditional co-deposition membrane. Combined with Figure 7 e, it can be found that the improvement of the membrane absorbance is positively correlated with the membrane surface temperature, and the higher the absorbance, the higher the membrane surface temperature. In addition, it can be found that as the volume of PVDF DMF solution added to water gradually increases during the preparation of PVDF nanoparticles, the surface temperature of the membrane finally obtained by the present invention gradually increases. However, Figure bc points out that the membrane surface temperature is not positively correlated with the evaporation rate of water and the photothermal conversion performance. The evaporation rate of water and the photothermal conversion performance gradually increase before the volume of PVDF solution added to water is 3mL (Example 2), and gradually decrease after reaching the maximum value at 3mL (Example 1) (Example 3-4). Therefore, the maximum evaporation amount of the polydopamine photothermal evaporation modified membrane obtained by the present invention is 1.68kg·m -2 ·h -1 Under these conditions, the photothermal conversion efficiency is 114.10%. Finally, Figure d shows the results of seawater desalination using Example 1. It can be seen that after photothermal evaporation, the salt content of various seawater has decreased by more than 2 orders of magnitude, indicating that this technology has excellent desalination performance.
[0065] in Figure 9 1 is a cross-sectional microscopic image of a film obtained in a relevant embodiment and a comparative example of the present invention; Figure 9 In the figure, a is a cross-sectional micrograph of the film obtained in Comparative Example 1; b is a cross-sectional micrograph of the film obtained in Example 2; c is a cross-sectional micrograph of the film obtained in Example 1; d is a cross-sectional micrograph of the film obtained in Example 3; e is a cross-sectional micrograph of the film obtained in Example 4; Figure 4 As shown in ab, Figure a shows that the microstructure of the commercial PVDF microfiltration membrane did not change significantly after co-deposition. As shown in Figure be, as the volume of PVDF DMF solution added to water gradually increased (from 1 mL to 8 mL) during the preparation of PVDF nanoparticles, the microstructure of the polydopamine modified membrane gradually changed from a loose porous structure to a dense non-porous structure. Therefore, Figure 8 The reason why the surface temperature of the membrane is not positively correlated with the evaporation rate of water (photothermal conversion performance) can be explained by Figure 4 and Figure 9Specifically, during the application of photothermal evaporation membrane, the membrane temperature needs to be increased to evaporate the water below it, and the evaporated water vapor needs to be transferred across the membrane to the gas phase. Therefore, the amount of water evaporation is not only related to the membrane temperature, but also to whether the water vapor can be transferred across the membrane. Figure 4 and Figure 9 From the membrane surface and membrane internal morphology described in , it can be seen that the internal structure of the membrane obtained in Example 3 and Example 4 gradually changes from a loose porous structure to a dense non-porous structure, which results in that in actual application, the water vapor evaporated from the membrane is difficult to be transferred to the gas phase through the pores in the membrane, and ultimately leads to the membrane surface temperature and the water evaporation rate (photothermal conversion performance) are not positively correlated.
[0066] The present invention provides a method for preparing an efficient polydopamine photothermal evaporation modified film, comprising the following steps:
[0067] Step 1: dissolving polymer A in solvent A to obtain solution A, and adding solution A dropwise into solvent B with stirring to obtain a dispersion of polymer A nanoparticles;
[0068] Step 2: assemble a commercial microfiltration membrane in a filtration cup and pour the polymer A nanoparticle dispersion into it, completely filter the polymer A nanoparticle dispersion to obtain polymer A nanoparticle aggregates on the surface of the commercial microfiltration membrane;
[0069] Step 3: Pour solvent A into a filtration cup containing a commercial microfiltration membrane and polymer A nanoparticle aggregates and completely filter out solvent A to obtain a swollen polymer A on the surface of the commercial microfiltration membrane; Pour solvent B into a filtration cup containing a commercial microfiltration membrane and a swollen polymer A and completely filter out solvent B to obtain a polymer A nanogel porous membrane on the surface of the commercial microfiltration membrane;
[0070] Step 4: dissolving dopamine hydrochloride in solvent B to obtain solution B; dissolving silane coupling agent A and anhydrous ferric chloride in solvent C to obtain solution C;
[0071] Step 5: Mix solution B and solution C and disperse them evenly to obtain solution D;
[0072] Step 6: Immerse the polymer A nanogel porous membrane with a commercial microfiltration membrane substrate in solution D and react with constant temperature and oscillation. After the reaction is completed, wash it to obtain a high-efficiency polydopamine photothermal evaporation modified membrane on the surface of the commercial microfiltration membrane.
[0073] Step 7: Immerse the high-efficiency polydopamine photothermal evaporation modified membrane with a commercial microfiltration membrane substrate into solvent D, completely dissolve the commercial microfiltration membrane with solvent D, and finally obtain a self-supporting high-efficiency polydopamine photothermal evaporation modified membrane, which is then preserved.
[0074] Example 1:
[0075] The method for preparing a high-efficiency polydopamine photothermal evaporation modified film comprises the following steps:
[0076] S101. Preparation of PVDF nanoparticle dispersion:
[0077] 0.6 g of polyvinylidene fluoride (PVDF) powder (molecular weight 0.4 MDa) was dissolved in 100 mL of N,N-dimethylformamide (DMF) solvent at 60°C with stirring to obtain a PVDF DMF solution; 3 mL of the solution cooled to 25°C was added dropwise to deionized water with stirring (addition rate 5 mL / min) to obtain a PVDF nanoparticle dispersion (all stirring rates were 150 rpm);
[0078] S102. Preparation of PVDF nanogel porous membrane:
[0079] A commercial nylon microfiltration membrane was assembled in a filtration cup, and the entire PVDF nanoparticle dispersion was poured into the filtration cup. The PVDF nanoparticle dispersion was completely filtered to obtain PVDF nanoparticle aggregates on the surface of the commercial nylon microfiltration membrane. 15 mL of DMF was poured into the filtration cup containing the commercial nylon microfiltration membrane and the PVDF nanoparticle aggregates and the DMF was completely filtered to obtain a PVDF swollen body on the surface of the commercial nylon microfiltration membrane. 200 mL of deionized water was poured into the filtration cup containing the commercial nylon microfiltration membrane and the PVDF swollen body and the deionized water was completely filtered to obtain a PVDF nanogel porous membrane on the surface of the commercial nylon microfiltration membrane (all filtration pressures were 0.95 bar).
[0080] S103. Preparation of polydopamine photothermal evaporation modified film with substrate
[0081] 0.2 g of dopamine hydrochloride was dissolved in 100 mL of deionized water at room temperature with stirring to obtain a dopamine hydrochloride aqueous solution; 0.1 g of a silane coupling agent (KH550) and 0.1 g of anhydrous ferric chloride were dissolved in 10 mL of 98 wt% ethanol with stirring at room temperature to obtain a solution C; the dopamine hydrochloride aqueous solution and the solution C were mixed and ultrasonically dispersed to obtain a solution D; a PVDF nanogel porous membrane with a commercial nylon microfiltration membrane substrate was immersed in the solution D and shaken in a constant temperature water bath at 50° C. and an oscillation frequency of 150 rpm for 20 hours. After the reaction was completed, it was repeatedly rinsed with deionized water until the eluent showed no color change, and a high-efficiency polydopamine photothermal evaporation modified membrane was obtained on the surface of the commercial nylon microfiltration membrane;
[0082] S104. Preparation of self-supporting polydopamine modified membrane by photothermal evaporation:
[0083] The high-efficiency polydopamine photothermal evaporation modified membrane with a commercial nylon microfiltration membrane substrate was immersed in 88 wt% formic acid, and the commercial nylon microfiltration membrane was completely dissolved by formic acid (after immersion for 24 hours, it was taken out and the formic acid was replaced. After replacement, the membrane was immersed in formic acid again for 24 hours, and the above operation process was repeated 4 times). Finally, a self-supporting high-efficiency polydopamine photothermal evaporation modified membrane was obtained and stored in deionized water.
[0084] Example 2:
[0085] The method for preparing a high-efficiency polydopamine photothermal evaporation modified film comprises the following steps:
[0086] S101. Preparation of PVDF nanoparticle dispersion:
[0087] 0.6 g of polyvinylidene fluoride (PVDF) powder (molecular weight 0.4 MDa) was dissolved in 100 mL of N,N-dimethylformamide (DMF) solvent at 60°C with stirring to obtain a PVDF DMF solution; 1 mL of the solution cooled to 25°C was added dropwise to deionized water with stirring (addition rate 5 mL / min) to obtain a PVDF nanoparticle dispersion (all stirring rates were 150 rpm);
[0088] S102. Preparation of PVDF nanogel porous membrane:
[0089] A commercial nylon microfiltration membrane was assembled in a filtration cup, and the entire PVDF nanoparticle dispersion was poured into the filtration cup. The PVDF nanoparticle dispersion was completely filtered to obtain PVDF nanoparticle aggregates on the surface of the commercial nylon microfiltration membrane. 15 mL of DMF was poured into the filtration cup containing the commercial nylon microfiltration membrane and the PVDF nanoparticle aggregates and the DMF was completely filtered to obtain a PVDF swollen body on the surface of the commercial nylon microfiltration membrane. 200 mL of deionized water was poured into the filtration cup containing the commercial nylon microfiltration membrane and the PVDF swollen body and the deionized water was completely filtered to obtain a PVDF nanogel porous membrane on the surface of the commercial nylon microfiltration membrane (all filtration pressures were 0.95 bar).
[0090] S103. Preparation of polydopamine photothermal evaporation modified film with substrate
[0091] 0.2 g of dopamine hydrochloride was dissolved in 100 mL of deionized water at room temperature with stirring to obtain a dopamine hydrochloride aqueous solution; 0.1 g of a silane coupling agent (KH550) and 0.1 g of anhydrous ferric chloride were dissolved in 10 mL of 98 wt% ethanol with stirring at room temperature to obtain a solution C; the dopamine hydrochloride aqueous solution and the solution C were mixed and ultrasonically dispersed to obtain a solution D; a PVDF nanogel porous membrane with a commercial nylon microfiltration membrane substrate was immersed in the solution D and shaken in a constant temperature water bath at 50° C. and an oscillation frequency of 150 rpm for 20 hours. After the reaction was completed, it was repeatedly rinsed with deionized water until the eluent showed no color change, and a high-efficiency polydopamine photothermal evaporation modified membrane was obtained on the surface of the commercial nylon microfiltration membrane;
[0092] S104. Preparation of self-supporting polydopamine modified membrane by photothermal evaporation:
[0093] The high-efficiency polydopamine photothermal evaporation modified membrane with a commercial nylon microfiltration membrane substrate was immersed in 88 wt% formic acid, and the commercial nylon microfiltration membrane was completely dissolved by formic acid (after immersion for 24 hours, it was taken out and the formic acid was replaced. After replacement, the membrane was immersed in formic acid again for 24 hours, and the above operation process was repeated 4 times). Finally, a self-supporting high-efficiency polydopamine photothermal evaporation modified membrane was obtained and stored in deionized water.
[0094] Example 2:
[0095] The method for preparing a high-efficiency polydopamine photothermal evaporation modified film comprises the following steps:
[0096] S101. Preparation of PVDF nanoparticle dispersion:
[0097] 0.6 g of polyvinylidene fluoride (PVDF) powder (molecular weight 0.4 MDa) was dissolved in 100 mL of N,N-dimethylformamide (DMF) solvent at 60°C with stirring to obtain a PVDF DMF solution; 5 mL of the solution cooled to 25°C was added dropwise to deionized water with stirring (addition rate 5 mL / min) to obtain a PVDF nanoparticle dispersion (all stirring rates were 150 rpm);
[0098] S102. Preparation of PVDF nanogel porous membrane:
[0099] A commercial nylon microfiltration membrane was assembled in a filtration cup, and the entire PVDF nanoparticle dispersion was poured into the filtration cup. The PVDF nanoparticle dispersion was completely filtered to obtain PVDF nanoparticle aggregates on the surface of the commercial nylon microfiltration membrane. 15 mL of DMF was poured into the filtration cup containing the commercial nylon microfiltration membrane and the PVDF nanoparticle aggregates and the DMF was completely filtered to obtain a PVDF swollen body on the surface of the commercial nylon microfiltration membrane. 200 mL of deionized water was poured into the filtration cup containing the commercial nylon microfiltration membrane and the PVDF swollen body and the deionized water was completely filtered to obtain a PVDF nanogel porous membrane on the surface of the commercial nylon microfiltration membrane (all filtration pressures were 0.95 bar).
[0100] S103. Preparation of polydopamine photothermal evaporation modified film with substrate
[0101] 0.2 g of dopamine hydrochloride was dissolved in 100 mL of deionized water at room temperature with stirring to obtain a dopamine hydrochloride aqueous solution; 0.1 g of a silane coupling agent (KH550) and 0.1 g of anhydrous ferric chloride were dissolved in 10 mL of 98 wt% ethanol with stirring at room temperature to obtain a solution C; the dopamine hydrochloride aqueous solution and the solution C were mixed and ultrasonically dispersed to obtain a solution D; a PVDF nanogel porous membrane with a commercial nylon microfiltration membrane substrate was immersed in the solution D and shaken in a constant temperature water bath at 50° C. and an oscillation frequency of 150 rpm for 20 hours. After the reaction was completed, it was repeatedly rinsed with deionized water until the eluent showed no color change, and a high-efficiency polydopamine photothermal evaporation modified membrane was obtained on the surface of the commercial nylon microfiltration membrane;
[0102] S104. Preparation of self-supporting polydopamine modified membrane by photothermal evaporation:
[0103] The high-efficiency polydopamine photothermal evaporation modified membrane with a commercial nylon microfiltration membrane substrate was immersed in 88 wt% formic acid, and the commercial nylon microfiltration membrane was completely dissolved by formic acid (after immersion for 24 hours, it was taken out and the formic acid was replaced. After replacement, the membrane was immersed in formic acid again for 24 hours, and the above operation process was repeated 4 times). Finally, a self-supporting high-efficiency polydopamine photothermal evaporation modified membrane was obtained and stored in deionized water.
[0104] Example 4:
[0105] The method for preparing a high-efficiency polydopamine photothermal evaporation modified film comprises the following steps:
[0106] S101. Preparation of PVDF nanoparticle dispersion:
[0107] 0.6 g of polyvinylidene fluoride (PVDF) powder (molecular weight 0.4 MDa) was dissolved in 100 mL of N,N-dimethylformamide (DMF) solvent at 60°C with stirring to obtain a PVDF DMF solution; 8 mL of the solution cooled to 25°C was added dropwise to deionized water with stirring (addition rate 5 mL / min) to obtain a PVDF nanoparticle dispersion (all stirring rates were 150 rpm);
[0108] S102. Preparation of PVDF nanogel porous membrane:
[0109] A commercial nylon microfiltration membrane was assembled in a filtration cup, and the entire PVDF nanoparticle dispersion was poured into the filtration cup. The PVDF nanoparticle dispersion was completely filtered to obtain PVDF nanoparticle aggregates on the surface of the commercial nylon microfiltration membrane. 15 mL of DMF was poured into the filtration cup containing the commercial nylon microfiltration membrane and the PVDF nanoparticle aggregates and the DMF was completely filtered to obtain a PVDF swollen body on the surface of the commercial nylon microfiltration membrane. 200 mL of deionized water was poured into the filtration cup containing the commercial nylon microfiltration membrane and the PVDF swollen body and the deionized water was completely filtered to obtain a PVDF nanogel porous membrane on the surface of the commercial nylon microfiltration membrane (all filtration pressures were 0.95 bar).
[0110] S103. Preparation of polydopamine photothermal evaporation modified film with substrate
[0111] 0.2 g of dopamine hydrochloride was dissolved in 100 mL of deionized water at room temperature with stirring to obtain a dopamine hydrochloride aqueous solution; 0.1 g of a silane coupling agent (KH550) and 0.1 g of anhydrous ferric chloride were dissolved in 10 mL of 98 wt% ethanol with stirring at room temperature to obtain a solution C; the dopamine hydrochloride aqueous solution and the solution C were mixed and ultrasonically dispersed to obtain a solution D; a PVDF nanogel porous membrane with a commercial nylon microfiltration membrane substrate was immersed in the solution D and shaken in a constant temperature water bath at 50° C. and an oscillation frequency of 150 rpm for 20 hours. After the reaction was completed, it was repeatedly rinsed with deionized water until the eluent showed no color change, and a high-efficiency polydopamine photothermal evaporation modified membrane was obtained on the surface of the commercial nylon microfiltration membrane;
[0112] S104. Preparation of self-supporting polydopamine modified membrane by photothermal evaporation:
[0113] The high-efficiency polydopamine photothermal evaporation modified membrane with a commercial nylon microfiltration membrane substrate was immersed in 88 wt% formic acid, and the commercial nylon microfiltration membrane was completely dissolved by formic acid (after immersion for 24 hours, it was taken out and the formic acid was replaced. After replacement, the membrane was immersed in formic acid again for 24 hours, and the above operation process was repeated 4 times). Finally, a self-supporting high-efficiency polydopamine photothermal evaporation modified membrane was obtained and stored in deionized water.
[0114] Comparative Example 1:
[0115] The steps for preparing the traditional polydopamine co-deposition modified membrane are as follows:
[0116] 0.2 g of dopamine hydrochloride was dissolved in 100 mL of deionized water at room temperature with stirring to obtain a dopamine hydrochloride aqueous solution; 0.1 g of a silane coupling agent (KH550) and 0.1 g of anhydrous ferric chloride were dissolved in 10 mL of 98 wt% ethanol with stirring at room temperature to obtain a solution C; the dopamine hydrochloride aqueous solution and solution C were mixed and ultrasonically dispersed to obtain a solution D; a commercial nylon microfiltration membrane was immersed in solution D and shaken in a constant temperature water bath at 50° C. and an oscillation frequency of 150 rpm for 20 hours. After the reaction was completed, it was repeatedly rinsed with deionized water until the eluate showed no color change to obtain a traditional polydopamine co-deposition modified membrane.
[0117] The parameters of Examples 1-4 and Comparative Example 1 as well as the film photothermal conversion and photothermal evaporation are shown in Table 1:
[0118] Table 1 Membrane preparation parameters and properties
[0119]
[0120] When the high-efficiency polydopamine photothermal evaporation modified film prepared by the method is actually used, the polydopamine photothermal evaporation modified film is placed at a 45° angle to the horizontal plane. At this time, under an illumination of 1 sun (1kW·m -2 ) under the conditions of photothermal conversion efficiency of 91.01-114.10%, and photothermal evaporation capacity of 1.34-1.68 kg·m -2 ·h -1 In this way, the problem that most photothermal evaporation films in the existing technology use PDA as an additive to bond high-absorbency polymers or inorganic materials, and there is little in-depth research on its photothermal evaporation performance, which limits the development of PDA in the field of photothermal evaporation and leads to the poor evaporation performance of existing photothermal evaporation films is solved.
[0121] The above disclosure is only a preferred embodiment of the present invention, and certainly cannot be used to limit the scope of the rights of the present invention. Ordinary technicians in this field can understand that all or part of the processes of the above embodiment and equivalent changes made in accordance with the claims of the present invention are still within the scope of the invention.
Claims
1. A method for preparing a highly efficient polydopamine photothermal evaporation modified film. It is characterized in that The following steps are involved: Step 1: dissolving polymer A in solvent A to obtain solution A, and adding solution A dropwise into solvent B with stirring to obtain a dispersion of polymer A nanoparticles; Step 2: assemble a commercial microfiltration membrane in a suction filtration cup and pour the polymer A nanoparticle dispersion into it, completely filter the polymer A nanoparticle dispersion to obtain polymer A nanoparticle aggregates on the surface of the commercial microfiltration membrane; Step 3: Pour solvent A into a suction cup containing a commercial microfiltration membrane and polymer A nanoparticle aggregates and completely filter out solvent A to obtain a swollen polymer A on the surface of the commercial microfiltration membrane; Pour solvent B into a suction cup containing a commercial microfiltration membrane and a swollen polymer A and completely filter out solvent B to obtain a polymer A nanogel porous membrane on the surface of the commercial microfiltration membrane; Step 4: dissolving dopamine hydrochloride in solvent B to obtain solution B; dissolving silane coupling agent A and anhydrous ferric chloride in solvent C to obtain solution C; Step 5, mixing solution B and solution C and dispersing them evenly to obtain solution D; Step 6: immerse the polymer A nanogel porous membrane with a commercial microfiltration membrane substrate into solution D and react with constant temperature oscillation, wash after the reaction is completed, and obtain a high-efficiency polydopamine photothermal evaporation modified membrane on the surface of the commercial microfiltration membrane; Step 7: Immerse the high-efficiency polydopamine photothermal evaporation modified membrane with the commercial microfiltration membrane substrate into solvent D, completely dissolve the commercial microfiltration membrane with solvent D, and finally obtain a self-supporting high-efficiency polydopamine photothermal evaporation modified membrane, which is then preserved.
2. The method for preparing a high-efficiency polydopamine photothermal evaporation modified film according to claim 1, characterized in that: The polymer A is at least one of polyvinylidene fluoride, polyethersulfone, polypropylene and polyamide, and has a molecular weight of 0.40Mda; The solvent B is at least one of water, ethanol and acetone; The solvent A is one or more of N,N-dimethylformamide, N-methylpyrrolidone, dimethylacetamide, and dimethyl sulfoxide; The solvent C is at least one of water, ethanol and acetone, with a mass fraction of at least one of 75%, 90% and 98%, and the amount is 5 to 15 mL; The solvent D is at least one of formic acid, N-methylpyrrolidone and dimethylacetamide, with a mass fraction of 88%.
3. The method for preparing a high-efficiency polydopamine photothermal evaporation modified film according to claim 2, characterized in that: In step one: The amount of the solvent A is as follows: polymer A: solvent A = 0.1-1.5 g: 50-200 mL; The amount of solvent B used is based on the amount taken from solution A: solvent B = 1-10 mL: 200 mL; In step 3: the amount of solvent A is 5 to 20 mL; In step 3: the amount of solvent B is 100-300 mL; In step 4, the amount of the solvent B is as follows: dopamine: solvent B = 0.1-0.5 g: 50-200 mL.
4. The method for preparing a high-efficiency polydopamine photothermal evaporation modified film according to claim 3, characterized in that: In step four: The dosage of anhydrous ferric chloride is as follows: anhydrous ferric chloride: solvent B = 0.05-0.5g: 50-200m; The silane coupling agent A is at least one of KH-550, KH-560, KH-570 and KH-580, and the dosage is silane coupling agent A: solvent C = 0.05-0.20 g: 50-200 mL.
5. The method for preparing a high-efficiency polydopamine photothermal evaporation modified film according to claim 4, characterized in that: In step one: When polymer A is dissolved in solvent A, it is carried out under heating and stirring conditions. Since polymer A is dissolved under heating conditions, the obtained solution A needs to be cooled to room temperature before being added dropwise to solvent B; Room temperature is 20-30℃; The stirring speed is 50-200 rpm; The dropping speed is 4-6 mL / min.
6. The method for preparing a high-efficiency polydopamine photothermal evaporation modified film according to claim 5, characterized in that: In step 2 and step 3: the filtration vacuum pressure is 0.55-1.00 bar; In step 4: the dissolution process is performed by stirring, and the stirring rate is preferably 150 rpm; In step 5: the dispersion method used for uniformly dispersing solution B and solution C is ultrasound, and the ultrasound conditions are: ultrasound power 120-180W, ultrasound time 2-5min; In step six: The constant temperature shaking method is a constant temperature water bath shaking, the temperature condition is 40-60°C, the shaking frequency is 90-180rpm, and the time is 18-24h; The cleaning method is to repeatedly rinse with deionized water until the eluent has no color change.
7. The method for preparing a high-efficiency polydopamine photothermal evaporation modified film according to claim 6, characterized in that: In step seven: the microfiltration membrane dissolution method is to immerse the membrane in solvent D for 24 hours, then take it out and replace the solvent, and then immerse the membrane in solvent D again for 24 hours after replacement, and repeat the above operation process 4 times.
8. The method for preparing a high-efficiency polydopamine photothermal evaporation modified film according to claim 7, characterized in that: In step seven: the method for preserving the high-efficiency polydopamine photothermal evaporation modified membrane is to immerse the membrane in deionized water, and replace the deionized water every 48 hours during the preservation process.
9. The method for preparing a high-efficiency polydopamine photothermal evaporation modified film according to claim 8, characterized in that: The commercial microfiltration membranes are nylon microfiltration membranes and polytetrafluoroethylene microfiltration membranes.
10. The method for preparing a high-efficiency polydopamine photothermal evaporation modified film according to claim 9, characterized in that: The prepared high-efficiency polydopamine photothermal evaporation modified membrane is applied in seawater desalination.
Citation Information
Cited By
Flexible polydopamine / enteromorpha photothermal film, preparation method and application thereof
CN120573792B